Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Discover a wealth of knowledge from professionals across various disciplines on our user-friendly Q&A platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Sure, let's solve the system of equations using the elimination method:
1. The system of equations is:
[tex]\[ \begin{array}{l} 5x + 6y = 12 \quad \text{(Equation 1)}\\ 2x - 4y = 8 \quad \text{(Equation 2)} \end{array} \][/tex]
2. First, we'll try to eliminate one of the variables by making the coefficients of [tex]\(x\)[/tex] or [tex]\(y\)[/tex] in both equations the same.
3. We’ll start by eliminating [tex]\(x\)[/tex]. The coefficients of [tex]\(x\)[/tex] in Equation 1 and Equation 2 are 5 and 2, respectively. To make them the same, we can multiply Equation 2 by 5 and Equation 1 by 2:
[tex]\[ 2(5x + 6y) = 2(12) \implies 10x + 12y = 24 \quad \text{(Equation 3)} \][/tex]
[tex]\[ 5(2x - 4y) = 5(8) \implies 10x - 20y = 40 \quad \text{(Equation 4)} \][/tex]
4. Now, subtract Equation 4 from Equation 3 to eliminate [tex]\(x\)[/tex]:
[tex]\[ (10x + 12y) - (10x - 20y) = 24 - 40 \][/tex]
Simplifying, we get:
[tex]\[ 10x + 12y - 10x + 20y = 24 - 40 \][/tex]
[tex]\[ 32y = -16 \][/tex]
Solving for [tex]\(y\)[/tex]:
[tex]\[ y = \frac{-16}{32} = -\frac{1}{2} \][/tex]
5. Now that we have the value of [tex]\(y\)[/tex], we can substitute it back into either Equation 1 or Equation 2 to find the value of [tex]\(x\)[/tex]. We'll use Equation 2:
[tex]\[ 2x - 4(-\frac{1}{2}) = 8 \][/tex]
Simplifying, we get:
[tex]\[ 2x + 2 = 8 \][/tex]
[tex]\[ 2x = 8 - 2 \][/tex]
[tex]\[ 2x = 6 \][/tex]
[tex]\[ x = \frac{6}{2} = 3 \][/tex]
6. Therefore, the solution to the system of equations is [tex]\(x = 3\)[/tex] and [tex]\(y = -\frac{1}{2}\)[/tex], which matches the point [tex]\((3, -0.5)\)[/tex].
So, the correct answer is [tex]\((3, -0.5)\)[/tex].
1. The system of equations is:
[tex]\[ \begin{array}{l} 5x + 6y = 12 \quad \text{(Equation 1)}\\ 2x - 4y = 8 \quad \text{(Equation 2)} \end{array} \][/tex]
2. First, we'll try to eliminate one of the variables by making the coefficients of [tex]\(x\)[/tex] or [tex]\(y\)[/tex] in both equations the same.
3. We’ll start by eliminating [tex]\(x\)[/tex]. The coefficients of [tex]\(x\)[/tex] in Equation 1 and Equation 2 are 5 and 2, respectively. To make them the same, we can multiply Equation 2 by 5 and Equation 1 by 2:
[tex]\[ 2(5x + 6y) = 2(12) \implies 10x + 12y = 24 \quad \text{(Equation 3)} \][/tex]
[tex]\[ 5(2x - 4y) = 5(8) \implies 10x - 20y = 40 \quad \text{(Equation 4)} \][/tex]
4. Now, subtract Equation 4 from Equation 3 to eliminate [tex]\(x\)[/tex]:
[tex]\[ (10x + 12y) - (10x - 20y) = 24 - 40 \][/tex]
Simplifying, we get:
[tex]\[ 10x + 12y - 10x + 20y = 24 - 40 \][/tex]
[tex]\[ 32y = -16 \][/tex]
Solving for [tex]\(y\)[/tex]:
[tex]\[ y = \frac{-16}{32} = -\frac{1}{2} \][/tex]
5. Now that we have the value of [tex]\(y\)[/tex], we can substitute it back into either Equation 1 or Equation 2 to find the value of [tex]\(x\)[/tex]. We'll use Equation 2:
[tex]\[ 2x - 4(-\frac{1}{2}) = 8 \][/tex]
Simplifying, we get:
[tex]\[ 2x + 2 = 8 \][/tex]
[tex]\[ 2x = 8 - 2 \][/tex]
[tex]\[ 2x = 6 \][/tex]
[tex]\[ x = \frac{6}{2} = 3 \][/tex]
6. Therefore, the solution to the system of equations is [tex]\(x = 3\)[/tex] and [tex]\(y = -\frac{1}{2}\)[/tex], which matches the point [tex]\((3, -0.5)\)[/tex].
So, the correct answer is [tex]\((3, -0.5)\)[/tex].
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.